Approximate controllability properties of the semilinear heat equation with lumped controls - Khapalov, Alexander (Zielona Góra: Uniwersytet Zielonogórski)
In this article, we study the global controllability properties of a one-dimensional semilinear heat equation with sublinear reaction term, governed in a bounded domain by internal lumped controls.
Keywords: semilinear heat equation; controllability; internal lumped control